Increasing productivity in paper bag manufacturing through lean manufacturing: a case study in Perú - Ramirez Palomino, Yoreli Nicole (2024)
The industry of small and medium-sized enterprises (SMEs) dedicated to the manufacturing of paper bags in Peru faces challenges related to production efficiency and quality management. Previous studies have shown that implementing Lean Manufacturing can significantly improve these aspects by optimizing processes and reducing waste. This study focused on production inefficiencies in SMEs in the sector, which manifest in high rates of non-conforming products and prolonged format change times, affecting the competitiveness and sustainability. To solve these problems, a production model based on Lean Manufacturing tools was proposed, specifically SMED, 5S, and Standardized Work. These tools were selected for their proven effectiveness in improving operational efficiency and reducing waste. The implementation of the model involved an initial diagnosis, followed by the systematic application of each tool, focusing on the transformation of internal to external tasks, workspace organization, and process standardization. The key results of the study included a 60% reduction in format change time, an increase in operational efficiency from 47.66% to 91.15%, and an improvement in product quality reflected in the decrease of defective products. These findings validate the effectiveness of the proposed model, demonstrating significant improvements in productivity and quality in paper bag manufacturing. The academic and socioeconomic impact of this research is notable, as it provides a practical and structured framework for addressing production inefficiencies in manufacturing SMEs. Waste reduction contributes to environmental sustainability, while improvements in productivity and quality strengthen the competitiveness of companies in the market. This study provides new evidence on the application of Lean Manufacturing in specific sectors. In conclusion, this research highlights the importance of adopting Lean Manufacturing methodologies to transform production processes and achieve continuous improvement in the manufacturing industry. Researchers and practitioners are encouraged to explore and adapt these methodologies in various industrial contexts, promoting innovation and sustainable growth.